Ectopic expression of a rice triketone dioxygenase gene confers mesotrione tolerance in soybean. Issue 7 (25th April 2022) - Dai, Shunhong; Georgelis, Nikolaos; Bedair, Mohamed; Hong, Yun‐Jeong; Qi, Qungang; Larue, Clayton T; Sitoula, Bikram; Huang, Wei; Krebel, Brian; Shepard, Michael; Su, Wen; Kretzmer, Keith; et al.
Abstract: BACKGROUND: Herbicide‐resistant weeds pose a challenge to agriculture and food production. New herbicide tolerance traits in crops will provide farmers with more options to effectively manage weeds. Mesotrione, a selective pre‐ and post‐emergent triketone herbicide used in corn production, controls broadleaf and some annual grass weeds via hydroxyphenylpyruvate dioxygenase (HPPD) inhibition. Recently, the rice HIS1 gene, responsible for native tolerance to the selective triketone herbicide benzobicyclon, was identified. Expression of HIS1 also confers a modest level of mesotrione resistance in rice. Here we report the use of the HIS1 gene to develop a mesotrione tolerance trait in soybean. RESULTS: Conventional soybean is highly sensitive to mesotrione. Ectopic expression of a codon‐optimized version of the rice HIS1 gene ( TDO ) in soybean confers a commercial level of mesotrione tolerance. In TDO transgenic soybean plants, mesotrione is rapidly and locally oxidized into noninhibitory metabolites in leaf tissues directly exposed to the herbicide. These metabolites are further converted into compounds similar to known classes of plant secondary metabolites. This rapid metabolism prevents movement of mesotrione from treated leaves into vulnerable emerging leaves. Minimizing the accumulation of the herbicide in vulnerable emerging leaves protects the function of HPPD and carotenoid biosynthesis more generally while providing tolerance to mesotrione. CONCLUSIONS: Mesotrione has a favorable environmental and toxicological profile. The TDO ‐mediated soybean mesotrione tolerance trait described here provides farmers with a new option to effectively manage difficult‐to‐control weeds using familiar herbicide chemistry. This trait can also be adapted to other mesotrione‐sensitive crops (e.g. cotton) for effective weed management. © 2022 Bayer Crop Science. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Transgenic soybean plants expressing the triketone dioxygenase gene ( TDO ), a codon optimized version of rice His1, rapidly convert mesotrione into noninhibitory metabolites to hydroxyphenylpyruvate dioxygenase and confer a commercial trait level of tolerance to mesotrione.